A Pilot Experience of Common European Infectious Diseases Curriculum for Medical Students: The IDEAL Summer School - Caroline, Charlier; Ogavu,Joseph; Nabankema,Evelyn; Omona,Venice; Cauda, Roberto (Future Microbiology, 2019)
Are we able to tackle the unprecedented global challenges in microbiology and infectious diseases? Uncontrolled antibiotic prescription and misuse led to the ever-rising emergence of multiresistant bacteria such as extended spectrum beta-lactamases (ESBL)-producing enterobacteria, multi and extremely-resistant mycobacteria [1,2]. Human activities, including extensive deforestation and climate change, have fueled the emergence of new pathogens like Zika virus, while massive migration and travel patterns, alongside other aspects of globalization, drive fast dissemination of these threats [3,4]. To address this ever-evolving scenario, education of the 14,000 European medical students [5] is of paramount importance [6], and our teaching work urgently requires re-appraisal. In sharp contrast with the huge efforts conducted in the last decades; improving European epidemiological surveillance, harmonizing antimicrobial susceptibility testing, developing joint therapeutic recommendations and research projects, European teaching initiatives have essentially stayed focused on postgraduate students. Undergraduate infectious diseases teaching remains heterogeneous in content, duration and methods, and is delivered at the local level without an inter-European emphasis. To foster students’ awareness of the upcoming challenges and to teach ways for handling those issues, we need to create a single community and abolish the current barriers hampering the circulation of students or teachers among